Protestant nationalists in Ireland, 1900-1923. By Conor Morrissey. Pp. xiv + 249 incl. 8 tables. Cambridge-New York: Cambridge University Press, 2019. £75. 978 1 108 47386 6 - Rafferty, Oliver P. 1956- (2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0022046920001852/resource/name/firstPage-S0022046920001852a.jpg
Keywords: Rezension